PREVALENSI STUNTING PADA BALITA DI WILAYAH KERJA PUSKESMAS SIDEMEN KARANGASEM - Muhammad Syairozi Hidayat; Gusti Ngurah Indraguna Pinatih (E-Jurnal Medika Udayana, 2017)
Stunting is identified through the indicator of Height for Age (H/A) < -2 SD based on the standard of WHO. According to Riskesdas 2007, Karangasem Regency had the highest prevalence of stunting amongst all regencies in Bali, accounted for 39,0%. Until now district of Sidemen Karangasem not conduct an evaluation of the problerm of stunting in children under five years of age. This study was conducted to find out the prevalence of stunting in children under five years of age at Sidemen Primary Health Care. A descriptive cross-sectional study conducted on 100 children in 8 Posyandu selected with consecutive sampling method. The data of stunting obtained through the measurement of height and adapted through the indicator of Height for Age according to the WHO, while the other data colected through interviews. The data were then analyzed descriptively. The prevalence of stunting in children under five years of age at Sidemen Primary Health Care was 35%. Children with stunting tends to be more prevalent in female (38.3%), lower mother education level (35.1%), history of non-exclusive breastfeeding (44.9%), and had a history of low birth weight (66.7). The prevalence of stunting in children under five in Sidemen primary helth care was high enough, so the prevention is required through public health nutrition program and maternal and child health program. Keywords: stunting, prevalence, children under five years of age, public health program, cross-sectional